Quantum information entropy of Eckart potential. Issue 19 (5th July 2016) - Pooja,; Kumar, R.; Kumar, G.; Kumar, R.; Kumar, Anil
Abstract: In this work, the position and momentum space information densities of the Eckart potential are graphically demonstrated and their properties are studied. The position space information densities have quite an asymmetric shape depending on the values of quantum numbers. The information entropy is obtained and Bialynicki‐Birula and Mycielski inequality is numerically saturated for some parameters of the potential. It is shown that the inequality is saturated with increasing potential depth. Abstract : Quantum information theory forms the framework for proper understanding of quantum communication and quantum computation. It measures the amount of information present in a system. The information entropy of one of the important exponential‐type Eckart potential is studied. The Fourier transform of this system would be interesting in different fields. The information density of the Eckart potential is graphically demonstrated and the Bialynicki‐Birula and Mycielski inequality is attempted to saturate.